An analysis of a secure communication for healthcare system using wearable devices based on elliptic curve cryptography. (29th October 2021) - Perumal, Pandiaraja; Subha, S.
In recent years, security and privacy are becoming more challenging which the major concerns in cloud are computing. The usable healthcare not only provides the accurate outcome but also maintains the confidentiality of medical results since the health information is highly sensitive. Nowadays, heart attack is considered as a more chronic disease and the use wearable sensors to monitor the patient continuously help the patient to take immediate medication with the help of SMS alerts through the patient's mobile phone. At present, mobile phones provide secure and private communications among healthcare systems. It performs the authentication and secure communication of patient, doctor and other healthcare entities involved in a healthcare scenario. The healthcare system aims to achieve a secure communication with high efficiency and low computational overheads. This paper focuses on various cryptographic algorithms and wireless technologies for secure and efficient communication.